DINAMIKA PERADABAN BUDAYA ISLAM - Clesea Marsakilahsari; Morena Ratudiah Allin; Shifa Salsabila; Neri Anjani; Tiara Pebriyanti; Fathimah Azzahra; Divani Chentia Sari; Az Zahra Sukma Nadia Ahmad (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to analyze the tradition of offerings (sesajen) and ceremonial prayers for the deceased (kenduri kiriman arwah) as a form of Islamic cultural acculturation among Javanese Muslim communities, as well as to understand the social and spiritual meanings and the factors that cause the tradition to be preserved to this day. This research employs a qualitative approach with a descriptive method through library research. Data were collected through a review of various literature sources, such as books, scientific journals, and research articles relevant to the topic of offering traditions, kenduri, and Javanese-Islamic acculturation. Data were analyzed descriptively and qualitatively using data reduction, data presentation, and conclusion drawing. The results show that the tradition of offerings and kenduri kiriman arwah is the result of acculturation between local Javanese culture that existed since the pre-Islamic period and Islamic teachings brought by the Wali (Islamic saints), especially Sunan Kalijaga. This tradition carries social, spiritual, and religious meanings, including as a form of respect for ancestors, a means of strengthening social solidarity and mutual cooperation, and as a medium for prayers and sending blessings to deceased family members. Factors causing this tradition to persist include the strong heritage of ancestral culture, the social values it contains, social pressure from the community, and the peaceful acculturation process that has taken place. However, there are also dynamic views among Muslim communities, where some consider this tradition as a cultural heritage that needs to be preserved, while others argue that certain elements need to be adjusted in accordance with the principles of monotheism (tauhid) in Islam. Thus, the tradition of offerings and kenduri kiriman arwah reflects the dynamics of Islamic cultural civilization in Indonesia, showing a harmonious interaction between religious values and local culture, and remains preserved as a cultural identity of Javanese Muslim communities to this day.